Analisis Perhitungan Harga Pokok Produksi dengan Metode Full Costing untuk Perkembangan UMKM Es Dawet Idola - Mubarokah Ari Yanti; Intan Novitasari Sah; Nurul Fadilah; Naurah Syifa; Ananda Silvi Nur Indriyanti; Alvin Ni’am Mahmud; Akhmad Khoirul Umam; Dian Fahriani (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
In this digital-based era, it is widespread in all circles to flock to become umkm actors from teenagers, adults and even parents. The growth of MSMEs in Indonesia continues to show a positive trend. The latest data from the Ministry of Cooperatives and SMEs notes that the number of MSMEs in 2024 will exceed 65 million units, with a very wide range of sectors, from culinary to digital technology. In this study, we will discuss in one MSME sector, namely in culinary, sometimes there are many MSMEs that only focus more on sales and income, for this reason, this study will discuss the analysis of the calculation of the cost of production in Es Dawet Idola MSMEs. This research uses a qualitative approach by conducting direct observations at the business location and in-depth interviews with business owners. The main objective of this research is to analyze the calculation of production costs of ice dawet idol so as to provide recommendations for the development of the business.